Meta‐analysis of prospective studies on the effects of nut consumption on hypertension and type 2 diabetes mellitus 对食用坚果对高血压和2型糖尿病的影响的前瞻性研究进行的meta分析. (29th July 2014) - Guo, Kai; Zhou, Zhiwen; Jiang, Yibo; Li, Wei; Li, Yigang
Abstract Background Inconclusive reports have been published on the consumption of nuts and the risk of hypertension and type 2 diabetes mellitus (T2DM). We performed a meta‐analysis of prospective studies to assess the effects of nut consumption on hypertension and T2DM risks. Methods A PUBMED and EMBASE database search was performed. Summary relative risks (SRRs) and 95% confidence intervals (CIs) were calculated using a random‐effects model. Q and I2 statistics were used to examine between‐study heterogeneity. Results A total of eight articles with nine prospective cohort studies (three hypertension studies and six T2DM studies) were selected. Using random effects models, we found that compared with never/rare consumers of nuts, those consuming >2 servings per week had an 8% lower risk of hypertension (SRR = 0.92, 95% CI: 0.87–0.97, P heterogeneity = 0. 590, I2 = 0%), while consumption of nuts at one serving per week had similar risk (SRR = 0.97, 95% CI: 0.83–1.13). In addition, nuts consumption was not associated with risk of T2DM (SRRs = 0. 98, 95% CI: 0.84–1.15; Pheterogeneity = 0. 008, I2 = 67.7%) on the basis of the highest versus lowest analysis. This null association was also shown in the dose‐response analysis. Conclusion Findings from this meta‐analysis indicate that consumption of nuts (>2 servings/week) may be inversely associated with hypertension risk, but not with T2DM risk.